Development and applications of forming-condition-based formability diagram for split concerns in stamping. (January 2015) - Zhang, Jianwei; Xu, Yanwu; Hu, Ping; Zhao, Kunmin
Abstract: This paper introduces an advanced, forming-condition-based formability diagram for accurately assessing the formability of complex stampings. The forming-condition-based formability diagram consists of a formability index that rationally define two curves (marginal line and safe line) and two zones (marginal zone and safe zone). The formability index measures deformation severity, tracks deformation history and predicts deformation trend. The safety factor, defined as the width of the marginal zone by means of the formability index, takes into account the forming conditions including deformation zone size, forming mode, bending process model, deformation history, metal flow pattern and post-necking deformation capacity of sheet metal. It is demonstrated that, rather than the traditional formability limit diagram, this formability diagram can more accurately quantify the formability status and can be used to determine the metal flow adjustment ranges for solving split problems. Its application to an automotive body side outer panel shows that it is a robust tool for formability engineering and troubleshooting through using numerical simulations and/or circle grid analysis.